Promotion And Service Quality On Consumer Satisfaction - Ningsih, Wida; Trisnadi, Dedy; Purwadi, Ricky Ekaristy; Chadijah, Siti (Economics and Digital Business Review, 2023)
This study aims to identify and analyze the influence of Price, Promotion, and Quality of Service on purchasing decisions at Hotel Savoy Homan. The phenomenon of the increase in the number of guests from May 2022 to April 2023 at Hotel Savoie Homan, guests who have stayed more than 5 times, and the good quality of service is the cornerstone of this study. The type of census performed is quantitative explanatory. The data analysis technique used is double linear regression. The sample determination method is Simple Random Sampling with a total sample of 87 people. The results of the research are partially positive and significant for the Purchase Decision, the Promotion has a positive and important influence on the Purchasing Decision and the Quality of Service positively influences the Purchains Decision. Simultaneously, the Price, Promotion, and Quality of the Service are capable of influencing a 39% Purchain Decision with the remaining 61% described by a variable or other factor.